Measuring the effect of environmental, social, and governance on sovereign funding costs - Naoko Nemoto; Lian Liu (Asian Development Bank Institute (ADBI), 2020)
This paper aims to examine the effect of Environmental, Social and Governance (ESG) performance on sovereign funding costs, with a focus on emerging countries, especially in Asia. We find that better ESG performance is associated with lower default risk, and therefore lower funding costs. We also discover that countries with better ESG performance tend to have higher credit ratings, an important benchmark of sovereign funding costs. Regarding the effects of each component of ESG, we note that the social factor is significant among Asian countries, while governance is significant among Organisation for Economic Co-operation and Development countries.
Keywords: G11; F34; 330; ESG performance; sovereign funding cost; credit rating